Respiratory infection with a bacterial pathogen attenuates CNS autoimmunity through IL-10 induction - MILLS, KINGSTON (My University, 2015)
Infection with viral or bacterial pathogens has been linked with the development of multiple sclerosis (MS), while infection with helminth parasites has been associated protection against MS and other autoimmune diseases. Here we have used a murine model of MS, experimental autoimmune encephalomyelitis (EAE), to examine the effect of infection with the respiratory pathogen Bordetella pertussis infection on development of CNS inflammation. The data demonstrate that infection of mice with B. pertussis significantly attenuates the clinical course of EAE induced by active immunization or cell transfer. This was reflected in a significant reduction in VLA-4 and LFA-1 expression on T cells and infiltration of IL-17+, IFN-γ+ and IFN-γ+IL-17+ CD4 T cells into the CNS. Infection with B. pertussis induced IL-10 production from dendritic cells in vitro and enhanced the frequency of IL-10-producing CD25-Foxp3+/− CD4+ T cells in vivo. Furthermore, the suppressive effects of B. pertussis infection on EAE were lost in IL-10−/− mice. Our findings demonstrate that a bacterial infection of the respiratory tract can attenuate EAE by promoting production of the anti-inflammatory cytokine IL-10 that may suppress licensing of autoaggressive T cells in the lungs, thereby preventing their migration into the CNS.
PUBLISHED
Keywords: viral or bacterial pathogens; viral or bacterial pathogens